STUDIES OF THE CONDITIONS OF THE INTERVAL SPEED CONTROL ROLLING UNHOOK ON AUTOMATED SLIDES - Kozachenko, D. M. (Science and Transport Progress, 2010)
Research of braking mode optimization under uncertainty of information about rolling down cuts and inaccurate realization of control actions by retarder positions is presented in the paper. The probability criterion for evaluation of conditions of sorting cuts is proposed.